From a new workplace to a new way of working: legitimizing organizational change. Issue 3 (26th July 2019) - Jemine, Grégory; Dubois, Christophe; Pichault, François
Abstract : Purpose: Several studies have recently documented projects of organizational transformation and modernization which, commonly clustered under the umbrella term "New Ways of Working" (NWoW), simultaneously entail material, technological, cultural and managerial dimensions. Academic contributions, however, have paid little attention to the mechanisms allowing such projects to progressively become legitimized in organizational discourses and practices. The purpose of this paper is to investigate the distinctive features of the legitimation process underlying the implementation of NWoW projects. Design/methodology/approach: This paper relies on a longitudinal, three-year analysis of a large insurance company. Data were collected through qualitative methods including semi-structured interviews (48), periods of observation (3 months) and document analysis (78). Findings: The paper develops a grounded and integrative framework of legitimation processes underlying "NWoW" change projects. The framework emphasizes four decisive operations of translation in "NWoW" design and implementation: translating material constraints into strategic opportunities; translating strategic opportunities into a quantitative business plan supported by the top management; translating compelling discourses around "NWoW" into an organizational machinery; and translating a transformation project into discourses of unequivocal success, conveyed by legitimate spokespeople within and beyond the organization. Originality/value: Besides contributing to the understanding of a managerial fashion, which has received little academic attention so far, the paper also offers an original integrative framework to account for legitimation processes that combines two theoretical approaches – the sociology of translation and research on institutionalist work.